Creation as Research: Contributions to the Reflection from the Experience of Universidad Central - Gutiérrez Mavesoy, Aleyda; Rodríguez Peña, Adriana (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The object of this article is the reflection about the notion of research on artistic formation programs and the possibilities of characterizing modes of knowledge production based on creation, specifically literary creation. First of all, we present some important aspects about the relation between re- search and creation in the field of the Arts. After this, we reflect creation as a field of production of new knowledge, and finally, we present the experience of the Literary Creation programs at Universidad Central